Length Of Time Return To Work In Workers With Low Back Pain And Associated Factors: Lamanya Waktu Kembali Bekerja Pada Pekerja Dengan Nyeri Punggung Bawah Dan Faktor Yang Berhubungan - Tri Mawanti, Wening; Soemarko, Dewi S.; Kekalih, Aria (Direktorat Penelitian, Pengabdian Masyarakat, Dan Kerjasama Universitas Binawan (DPPMK Universitas Binawan), 2023)
Low back pain is one of the musculoskeletal disorders often associated to work. Based on previous research, 70.3% low back pain was found in manual handling workers and 22.98% in female nurses in hospital wards. The effects of low back pain are disability, decreased productivity and attendance rate, and loss of working hours. Returning to work as soon as possible after illness in a certain capacity is a highly recommended action. Until now in Indonesia there is no data on the length of time return to work on workers with low back pain and related factors. This study used cross-sectional design to determine the length of time return to work and its relation to individual factors, work, and work environment. It used the Oswestry questionnaire and the population is workers who have low back pain and treated in a hospital, given sick leave, by the doctor as outpatient or inpatient. Workers with low back pain treated at the hospital (November 2016-April 2017), obtained a doctor's rest and or hospitalization letter amounting to 40 people (total sampling). The average value of the duration of return to work is 3 days (1-15 days) although clinical complaints have not fully disappeared. Factors relating to the length of the return to work were age (OR 9,71, 95% CI 1.08-87.31) and disability level before treatment (OR 2.50, 95% CI1.25-4.99). Length of time return to work due to low back pain is 3 days and has association to age and disability level.